Letter - Churchill, Victor Peter Spencer, Viscount, 1890-1973
041-0177-001 SPANISH MEDICAL AID COMMITTEE President: Dr. CHRISTOPHER ADDISON Chairman: Dr. H.B. MORGAN Treasurers: Viscountess HASTINGS Professor MARRACK Viscount CHURCHILL Hon. Secretary: Dr. CHARLES BROOK, L.C.C. 24 NEW OXFORD STREET W.C.1 Telephone: HOLborn 0605 August 20th 1936. HVT Dear Mr Tewson, We understand from our colleagues who met representatives of the National Council of Labour yesterday that promise of help was given in the matter of securing passports for members of the unit. Difficulty has arisen in connection with the passports of Miss Silverthorne and Miss Bell who bring this letter and we will appreciate any assistance that you may be able to give so as to enable them to leave with the rest of the party on Sunday evening. Yours sincerely, Churchill 292/946/41/177